Carbonization-cured high-strength gangue-based low-carbon, fire-free grass-planting bricks and preparation method thereof
By optimizing the treatment of coal gangue raw materials and slurry modification, combined with carbonization maintenance technology, low-carbon burn-free grass-planting bricks of coal gangue-based good strength and durability have been prepared, solving the problems of low strength, low utilization rate and high carbon emissions in the existing technology, and achieving the goals of efficient resource utilization and environmental protection.
Patent Information
- Application Number
- CN202310021597.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-01-07
AI Technical Summary
The existing coal gangue-free bricks are made of low strength, low utilization rate of coal gangue, high energy consumption and carbon emissions, and poor plant adaptability.
The preparation method of high-strength coal gangue-based, low-carbon, burn-free grass-planted bricks is adopted to improve the strength and plant adaptability of the bricks by optimizing technical means such as coal gangue raw material treatment, slurry modification and carbonization maintenance.
It has achieved high-strength and durability without burning grass-planting bricks, improved the utilization rate of coal gangue, reduced carbon emissions, enhanced plant adaptability, and conformed to the concept of circular economy and environmental protection.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to a carbonization-cured high-strength gangue-based low-carbon, fire-free grass-planting brick and a preparation method thereof. Background Art
[0002] my country is the world's largest coal producer and consumer. With the mining and use of coal, a large amount of coal gangue is produced. At present, my country's annual coal gangue emissions are about 800 million tons. There are about 1,900 coal gangue mountains in my country, with a stockpile of about 5 billion to 6 billion tons, occupying about 15,000 hectares of land. Due to the large production base and the lack of key common technologies for large-scale and high-value utilization, coal gangue has not been efficiently resourced, which has brought great pressure to environmental protection.
[0003] Making bricks from coal gangue is one of the main directions of coal gangue resource utilization. The technology of using coal gangue to completely or partially replace clay and adopting appropriate firing processes to produce sintered bricks has matured in my country, and the product quality of coal gangue bricks can reach or even exceed the quality standards of traditional clay bricks. However, in addition to the need for special sintering kilns, sintered brick making also has problems such as high energy consumption in the sintering process, large environmental pollution, and high carbon emissions. Therefore, the preparation of unfired bricks from coal gangue is a new development direction. Wu Hong et al. (Research on the cementing properties of unfired bricks based on activated coal gangue, Bulletin of the Silicate, 2017, Vol. 36, No. 1) used activated or uncalcined coal gangue as the main raw material, supplemented with cement, slag and other materials to prepare unfired bricks. The unfired bricks were cured under steam, and the performance of the prepared unfired bricks can reach the technical requirements of MU15 non-fired ordinary bricks. Jin Changguo (Using coal gangue to produce unburned bricks, Coal Processing and Comprehensive Utilization, 1998, Issue 2) uses coal gangue, cement, river sand, etc. to produce unburned hollow blocks and unburned interlocking floor tiles, with compressive strengths of 5.2MPa and 15.7MPa respectively. Patent CN201710093595.3 uses cement, coal gangue, fly ash, etc. to prepare coal gangue unburned bricks. Although the compressive strength can reach more than 35MPa, the unburned bricks need autoclave curing (temperature of 31-35℃, pressure of 1.2-1.5MPa, time of 6-9 hours), the process is complicated, and the energy consumption and carbon emissions are high. In the existing technology of using coal gangue to prepare unburned bricks, the utilization rate of coal gangue is low, and the strength of unburned bricks is low when cured at room temperature and steam. The autoclave curing method will complicate the production process, increase energy consumption and carbon emissions, and reduce safety. At the same time, using silicate cement as a cementitious material has problems such as high cost, high carbon emissions, and high energy consumption.
[0004] The problem of poor plant adaptability is that the silicate cement unfired grass bricks have a high pH value of 13-14 in the pore solution of the silicate cement hardened slurry. When it is prepared into porous concrete and slope protection bricks for ecological slope protection, it is not conducive to the growth of alkali-intolerant plants. In order to improve the applicability of plants, ferrous sulfate is often sprayed to reduce the pH value of the concrete surface. However, this method only changes the surface pH value, and the internal pH value does not decrease significantly. The long-term impact on soil alkalinity is still large. Therefore, the plant adaptability of unfired grass bricks needs to be further improved. Summary of the invention
[0005] The present invention provides a carbonization-cured high-strength gangue-based low-carbon unfired grass-planting brick and a preparation method thereof, aiming to solve the problems of low strength of unfired bricks, low utilization rate of gangue, high energy consumption and carbon emissions, high cost, etc., and to improve plant adaptability to achieve efficient resource utilization of gangue.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick is designed, which is made of the following raw materials in parts by weight: 260-520 parts of coal gangue-based polymer, 624-936 parts of coal gangue fine aggregate, 1144-1714 parts of slurry-coated coal gangue coarse aggregate, and 200-300 parts of water.
[0008] The gangue-based polymer is made of the following raw materials in parts by weight: 110-220 parts of solid waste ultrafine powder, 110-220 parts of burned coal-based solid waste ultrafine powder, 0-22 parts of nano gangue powder, 10-118 parts of alkaline substances, 0-45 parts of gypsum, and 0-25 parts of inorganic salts;
[0009] The slurry-coated coal gangue coarse aggregate is prepared by the following method: immersing coal gangue coarse aggregate particles with a particle size of 5mm to 15mm in coal gangue-based polymer slurry, shaking and then standing, and filtering out the slurry after repeating 1 to 2 times, and then curing in a cool place for 25 to 30 days, the curing temperature is ≥15°C, and the material is kept in a wet state during the curing period; the coal gangue-based polymer slurry is composed of coal gangue-based polymer and water in a mass ratio of 1:0.3 to 0.5.
[0010] The inorganic salt is at least one of carbonate, nitrate, chloride, metasilicate, silicate and water glass.
[0011] In terms of weight percentage, the solid waste ultrafine powder has the following specific surface area ≥ 600m 2 / kg of fine powder composition: 50-100% ultrafine granulated blast furnace slag powder, 0-50% ultrafine fly ash.
[0012] The alkaline substance has a specific surface area of ≥600m2 / kg of fine powder composition: 50-100% carbide slag, 0-50% ultrafine steel slag powder, and 0-50% red mud.
[0013] The specific surface area of the nano-coal gangue powder is > 240m 2 / g, particle size <30nm;
[0014] The gypsum is at least one of desulfurized gypsum and phosphogypsum.
[0015] In terms of weight percentage, the ultrafine powder of the burned coal-based solid waste is composed of the following specific surface area ≥ 600m 2 / kg of fine powder composition: 50-100% calcined coal gangue ultrafine powder, 0-50% calcined coal slime ultrafine powder.
[0016] The preparation method of the calcined coal gangue ultrafine powder is as follows:
[0017] The coal gangue powder is mixed with 0-20% carbide slag and ground to a specific surface area of ≥300m 2 / kg, the powder under the sieve is calcined at 730-750℃ for 25-35min, and then ground to a specific surface area of ≥600m 2 / kg; the gangue powder is obtained by crushing washed gangue into particles less than 5mm by a jaw crusher and / or a roller crusher, and then grinding it in a ball mill for 30 to 90 minutes and then sieving out particles with a particle size greater than 0.212mm to obtain a powder.
[0018] The preparation method of the calcined coal slime ultrafine powder is as follows:
[0019] Take the coal slime produced in the coal washing process and mix it with 0-20% carbide slag, calcine it at 600℃ for 25-35min, and then grind it to a specific surface area of ≥600m 2 / kg.
[0020] The coal gangue fine aggregate is a granular material with a particle size of less than 5 mm obtained by crushing and screening the excavated coal gangue.
[0021] The method for preparing the carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting bricks comprises the following steps:
[0022] A. Preparation of premix: Prepare the raw materials according to the raw material ratio, first pour the remaining raw materials except the gangue fine aggregate and the slurry-coated gangue coarse aggregate into a forced mixer for stirring, first stir slowly for 30 seconds, then add the gangue fine aggregate and the slurry-coated gangue coarse aggregate at a uniform speed, continue to stir slowly for 60 seconds, let it stand for 60 seconds, and then stir quickly for 60 seconds to complete the preparation of the premix;
[0023] B. Forming of unburned grass-planting bricks: Pour the premix into the mold, turn on the vibration pump at the bottom of the brick-making machine until the premix is at the same level as the upper edge of the mold, and then turn off the vibration pump; move the pressing plate back to the initial position and open the pressing plate control valve to allow the pressing plate to move downward and fully contact the premix; turn on the upper vibration pump, and turn off the vibration pump when the pressing plate moves down to the set position, demold, and obtain the bricks;
[0024] C. Curing of unfired grass bricks: The prepared unfired grass bricks are left to stand for 24 hours. After being formed, they are wrapped with plastic wrap and placed in an unventilated room at 15-25°C for curing for 3-5 days. Then, they are carbonized and cured in a sealed container for 3-5 days. The carbon curing conditions are as follows: temperature 15-25°C, humidity 50%-70%, and CO2 volume fraction >15%.
[0025] Compared with the prior art, the main beneficial technical effects of the present invention are:
[0026] The raw material components in the present invention work synergistically, so that the obtained carbonized cured high-strength coal gangue-based low-carbon and fire-free grass-planting bricks have high strength, good durability such as anti-freezing, anti-weathering, anti-carbonization, and water resistance, and good plant adaptability; the present invention has a high utilization rate of coal gangue, low carbon emissions during the preparation process, complies with the circular economy and environmental protection concepts, and has good environmental coordination.
[0027] The coordination mechanism between the main raw materials in the present invention is briefly described as follows:
[0028] 1. Mechanism of optimizing treatment of coal gangue raw materials: Coal gangue is composed of a variety of minerals. The mineral composition of coal gangue produced in different regions and different mining processes is different, and even varies greatly. Its potential activity also varies greatly. Therefore, it is necessary to optimize the treatment to meet the technical requirements of high-strength coal gangue for high-quality coal gangue powder. Clay minerals such as kaolinite, montmorillonite and illite in coal gangue have low hardness (Mohs hardness value is between 1 and 2.5), which is significantly lower than quartz, calcite, pyrite, hematite and other minerals. Minerals with low hardness are easier to become smaller powder particles than minerals with high hardness during crushing and grinding. Based on the significant difference in hardness between clay minerals and other minerals, the present invention crushes the washed coal gangue into particles less than 5 mm by a jaw crusher and a roller crusher, and grinds it in a ball mill for 30 to 90 minutes, and uses a 70-mesh sieve to remove particles larger than 0.212 mm. The content of clay minerals such as kaolinite in the remaining powder is increased by more than 30% compared with that before treatment; the main minerals of the high-quality coal gangue powder finally obtained are clay minerals such as kaolinite, montmorillonite and illite, and their potential activity can be greatly stimulated by mechanical activation and thermal activation; the obtained high-quality coal gangue powder is further calcined at high temperature to appear yellow, and is ground to a specific surface area of ≥600m 2 / kg, and the 28d activity index is more than 35% higher than that of untreated coal gangue.
[0029] 2. Principle of modification of coal gangue coarse aggregate by coating: Compared with ordinary natural aggregates, coal gangue has low hardness, high crushing value and poor firmness. As aggregate of unburned grass-planting bricks, it is easy to cause low brick strength. In order to improve the mechanical properties of coal gangue coarse aggregate, the present invention adopts coal gangue base polymer slurry to coat and modify the coal gangue coarse aggregate. Geopolymer is a silicon-aluminum raw material that undergoes dissolution-reconstruction-condensation and other processes under the action of an activator to generate an amorphous colloid. The colloid has a three-dimensional network structure and has excellent bonding properties, compressive strength and chemical stability. After coating, a layer of geopolymer shell with excellent mechanical properties and durability is formed on the surface of the coal gangue coarse aggregate, and it has good bonding with the coal gangue coarse aggregate. In addition, coal gangue is prone to microcracks during the crushing process. After the geopolymer slurry enters the microcracks, the reaction products generated can fill the microcracks, making the microstructure more compact. The above-mentioned slurry coating treatment can significantly enhance the mechanical properties of the gangue coarse aggregate, reduce the crushing value by more than 40%, and reduce the mass loss by more than 50% in the firmness test. Based on the above mechanism, the unburned grass bricks can have higher mechanical and durability properties.
[0030] 3. Carbonization curing modification mechanism: During the carbonization curing process of the unfired grass bricks, alkaline or calcium-containing substances (CSH gel, etc.) such as carbide slag and steel slag powder in the mixed material system react with CO2 at a certain humidity to generate carbonates such as calcium carbonate, which are deposited in the pores and microcracks to fill the pores and microcracks, making the microstructure of the unfired grass bricks denser and stronger.
[0031] 4. Mechanism of action of nano-gangue: The reinforcing effect of nano-gangue on fire-free grass bricks is mainly attributed to the filling effect, volcanic ash effect and nucleation effect. The filling effect is that nano-gangue, as a nano-scale micro-aggregate, forms a close stacking system with ultrafine powder particles, gangue fine aggregate, and slurry-coated gangue coarse aggregate. The particle size of nano-gangue reaches the nanoscale, which can better fill the nano-scale voids and make the stacking system denser. The volcanic ash effect refers to the fact that the active silicon oxide, aluminum oxide, and iron oxide in nano-gangue can react with carbide slag and inorganic salts to generate hydrated calcium silicate gel, hydrated calcium aluminate, and hydrated calcium iron gel to produce cementing ability; hydrated calcium aluminate can also react with dihydrate gypsum in the by-product gypsum to generate calcium sulfonate, which fills fine cracks. The nucleation effect refers to the presence of a large number of broken bonds and structural defects on the surface of nano-coal gangue, which has a strong ability to adsorb ions and can serve as a new nucleation site, causing the hydration product to transform from uniform nucleation to non-uniform nucleation, greatly reducing the nucleation barrier, and making it easy for the hydration product to crystallize and grow. Based on the above mechanism, the use of nano-coal gangue makes the prepared geopolymer have better performance.
[0032] 5. Mechanism of improving plant adaptability: In the geopolymer system of the present invention, OH in the alkaline substance -Participates in the dissolution-reconstruction-condensation reaction of geopolymers. After the reaction, the OH - The concentration is low and the pH value is low (about 12), which is significantly lower than the pH value of the pore solution of the hardened silicate cement slurry. In addition, during the carbonation curing stage, CO2 dissolves in water in the presence of water to form carbonic acid, and the carbonic acid reacts with highly alkaline substances to further reduce the pH value to below 8, which greatly improves the plant adaptability of the fire-free grass bricks.
[0033] 6. Ultrafine powder effect of solid waste: When solid waste is ultrafinely crushed, the material is subjected to strong impact, friction, shearing and collision, and the mineral crystals will break along the weakest bonding point in the crystal structure; the molecular arrangement and distribution structure on its surface changes, resulting in a peculiar surface and interface effect; as the particle size of ultrafine powder decreases (median diameter is about 5μm), the surface area increases sharply (≥600m 2 / kg), causing the number of surface atoms to increase rapidly, the number of unsaturated bonds to increase, and greatly increasing the activity of the particles, thereby greatly improving the reaction degree of the system, so that the prepared geopolymer has a higher reaction degree and better performance.
[0034] 7. Mechanism of improving the activity of coal-based solid waste after calcium addition: Coal-based solid wastes such as coal gangue and coal slime are calcined at 500-900°C by adding carbide slag, and clay minerals are dehydrated to generate amorphous products, thereby increasing the degree of participation of coal-based solid waste in the reaction; Ca(OH)2 in carbide slag reacts with part of Al2O3 and SO3 to generate CaO·Al2O3 and CaSO4, further increasing the degree and speed of the reaction; after calcium addition and calcination of coal-based solid waste, the reaction activity is greatly improved and the reaction time is greatly shortened; Based on the above mechanism, the raw materials are rationally compounded to make the prepared geopolymer have higher mechanical and durability properties.
[0035] 8. Mechanism of synergistic effect of multi-source solid waste: The synergistic effect of multi-source solid waste increases the reaction speed and order, greatly improving the strength of the matrix. The synergistic effect mainly includes four parts: ① Thermal activation, mechanical activation and chemical activation. The synergistic effect of multiple activation methods: calcined coal gangue and calcined coal slime are both solid wastes that are thermally activated by calcination, and clay minerals undergo dehydration reactions to form amorphous silicon-aluminum products, which have higher anti-activity; solid waste ultrafine powders and burnt coal-based solid waste ultrafine powders are mechanically ground, and the specific surface area is greater than 600m 2 / kg, exerting a mechanical activation effect, thus having higher activity; under the combined action of various anions and cations of various chemical stimulants, it has a higher chemical activation effect; ② Synergistic effect of chemical components and mineral components of multi-source solid waste: various solid wastes have different chemical components and mineral components, showing a composite super-superposition effect, which greatly improves the reaction rate and reaction degree; ③ Synergistic effect of multiple stimulants: stimulants such as carbide slag, by-product gypsum, and inorganic salts each provide different ions and alkaline environments for the system. Under the alkaline environment, these ions interact with each other in a mutually promoting manner, greatly accelerating the reaction process and degree of dissolution, reconstruction and polymerization of solid waste components; ④ Synergistic effect of multiple products: multi-source solid waste generates a wide variety of products under various activation methods, mainly amorphous colloids such as alkali metal aluminum silicate gel, CSH gel, CASH gel, CNASH gel, and crystalline minerals such as zeolite minerals, feldspar minerals, and calcium sulfonate. Various amorphous colloids and various crystalline minerals are interlocked, filled, reinforced, and toughened with each other, so that the prepared geopolymer has higher strength and durability. DETAILED DESCRIPTION
[0036] The specific implementation modes of the present invention are described below in conjunction with examples. However, the following examples are only used to illustrate the present invention in detail and are not intended to limit the scope of the present invention in any way.
[0037] Unless otherwise specified, the instruments and equipment involved in the following embodiments are all conventional instruments and equipment; the preparation methods involved are all conventional methods unless otherwise specified.
[0038] Materials involved in the following examples: The maximum particle size of ultrafine solid waste powder is less than 20μm; the 28d activity index of ultrafine granulated blast furnace slag powder is ≥120%; the 28d activity index of ultrafine fly ash is ≥90%; the 28d activity index of ultrafine calcined coal gangue powder is ≥110%; the 28d activity index of ultrafine calcined coal slime powder is ≥115%; the particle size of nano-gangue powder is less than 30nm; the calcium hydroxide content in carbide slag is greater than 85%; the specific surface area of ultrafine steel slag powder and red mud is ≥600m 2 / kg; the content of calcium sulfate dihydrate in desulfurized gypsum is greater than 92%; the content of clay minerals in high-quality coal gangue powder is above 70%; the inorganic salts are all industrial-grade products that meet the relevant national standards; the coal gangue fine aggregate is obtained by crushing and screening the coal gangue for excavation, and the particle size is less than 5mm.
[0039] In the following examples, the slurry-coated coal gangue coarse aggregate is prepared by the following method:
[0040] ① The excavated coal gangue is crushed and screened, and the particles with a size range of 5mm to 15mm are the coarse aggregate of coal gangue;
[0041] ② Soak the gangue coarse aggregate in geopolymer slurry (the mass ratio of gangue base polymer to water is 1:0.3-0.4), the slurry completely covers the gangue coarse aggregate, vibrate on a vibration table for 90 seconds, let it stand for 60 seconds, vibrate again for 90 seconds, and let it stand for 60 seconds;
[0042] ③ Use a sieve to filter out the slurry, then place it in a cool place, turn it over 3 to 5 times within 1 day, and the first two turns should be done within 3 hours to avoid particle sticking;
[0043] ④ Continue to place in a cool place (temperature above 15℃). If the surface of the particles is dry, spray to make the surface moist for up to 28 days.
[0044] In the following examples, high-quality coal gangue powder is prepared by the following method: washed coal gangue is crushed to particles less than 5 mm by a jaw crusher and a roller crusher, and then ground in a ball mill for 30 minutes, and particles larger than 0.212 mm are sieved with a 70-mesh sieve to obtain high-quality coal gangue powder.
[0045] The ultrafine powder of coal gangue is prepared by the following method: high-quality coal gangue powder is mixed with 15% calcium carbide slag and ground to a specific surface area of ≥300m 2 / kg, the powder under the sieve was calcined at 749℃ for 30min, and then ground to a specific surface area of ≥600m 2 / kg, obtained after natural cooling.
[0046] The calcined coal slime ultrafine powder is prepared by the following method: coal slime is mixed with 15% carbide slag and ground to a specific surface area of ≥300m 2 / kg, calcined at 600℃ for 30min, and then ground to a specific surface area of ≥600m 2 / kg, obtained after natural cooling.
[0047] The fire-free grass bricks in the following examples all include the following preparation steps:
[0048] (1) Preparation of premix: First, the weighed raw materials (except fine aggregate of coal gangue and coarse aggregate of coal gangue coated with slurry) are poured into a forced mixer for stirring. The stirring is divided into two stages. In the first stage, the mixer stirs slowly for 30 s, then adds fine aggregate of coal gangue and coarse aggregate of coal gangue coated with slurry at a uniform speed, continues to stir slowly for 60 s, then stands for 60 s, and then stirs quickly for 60 s to complete the preparation of the premix.
[0049] (2) Preparation of fire-free grass-planted brick blanks: Pour the premix into the mold, turn on the lower vibration pump until the premix and the upper edge of the mold are on the same horizontal plane, and then turn off the vibration pump; move the pressing plate back to the initial position and open the pressing plate control valve to allow the pressing plate to move downward and fully contact with the premix; turn on the upper vibration pump, and turn off the vibration pump when the pressing plate moves down to the set position, demold, and obtain the brick blanks.
[0050] (3) Curing of unfired grass bricks: The prepared unfired grass bricks are left to stand for 24 h. After being formed, they are wrapped with plastic wrap and placed in an unventilated room at (20±5)℃ for curing for 3 to 5 days. Then, they are carbonized and cured in a sealed container for 3 to 5 days. The carbonization curing conditions are as follows: temperature (20±5)℃, humidity 50% to 70%, and CO2 volume fraction greater than 15%.
[0051] The following performance testing or evaluation methods for unburned grass bricks are involved: The compressive strength of unburned grass bricks is carried out in accordance with "Concrete Solid Bricks" (GB / T 21144-2007). The density grade, water absorption rate, drying shrinkage rate, carbonation coefficient and softening coefficient of unburned grass bricks are tested in accordance with the methods specified in "Concrete Test Blocks and Bricks Test Methods" (GB / T 4111-2013). Frost resistance is carried out in accordance with "Concrete Blocks and Bricks Test Methods" (GB / T 4111-2013) and "Concrete Solid Bricks" (GB / T21144-2007). Frost tests are carried out in accordance with the relevant provisions of "Wall Brick Test Methods" (GB / T2542-2012).
[0052] Example 1 A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick is made of the following raw materials in parts by weight:
[0053] 395 parts of gangue-based polymer, 594 parts of gangue fine aggregate, 1382 parts of slurry-coated gangue coarse aggregate, and 176 parts of water. Among them, the gangue-based polymer cementitious material is made of the following raw materials in parts by weight: 123 parts of ultrafine granulated blast furnace slag powder, 167 parts of calcined gangue ultrafine powder, 35 parts of ultrafine steel slag powder, 35 parts of carbide slag, and 35 parts of desulfurized gypsum. In the preparation process of slurry-coated gangue coarse aggregate, the mass ratio of gangue-based polymer to water is 1:0.38.
[0054] Example 2 A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick is made of the following raw materials in parts by weight:
[0055] 415 parts of gangue-based polymer, 599 parts of gangue fine aggregate, 1472 parts of slurry-coated gangue coarse aggregate, and 166 parts of water. Among them, the gangue-based polymer cementitious material is made of the following raw materials in parts by weight: 126 parts of ultrafine granulated blast furnace slag powder, 165 parts of calcined gangue ultrafine powder, 40 parts of ultrafine steel slag powder, 63 parts of carbide slag, and 21 parts of calcium chloride. In the preparation process of slurry-coated gangue coarse aggregate, the mass ratio of gangue-based polymer to water is 1:0.35.
[0056] Example 3 A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick is made of the following raw materials in parts by weight:
[0057] 520 parts of gangue-based polymer, 575 parts of gangue fine aggregate, 1342 parts of slurry-coated gangue coarse aggregate, and 165 parts of water. Among them, the gangue-based polymer gelling material is made of the following raw materials in parts by weight: 196 parts of ultrafine granulated blast furnace slag powder, 206 parts of calcined gangue ultrafine powder, 58 parts of calcined coal slime ultrafine powder, 50 parts of calcium carbide slag, and 10 parts of sodium carbonate. In the preparation process of slurry-coated gangue coarse aggregate, the mass ratio of gangue-based polymer to water is 1:0.38.
[0058] Example 4 A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick is made of the following raw materials in parts by weight:
[0059] 467 parts of gangue-based polymer, 563 parts of gangue fine aggregate, 1438 parts of slurry-coated gangue coarse aggregate, and 168 parts of water. Among them, the gangue-based polymer cementitious material is made of the following raw materials in parts by weight: 109 parts of ultrafine granulated blast furnace slag powder, 177 parts of calcined gangue ultrafine powder, 42 parts of calcined coal slime ultrafine powder, 50 parts of carbide slag, 56 parts of red mud, and 33 parts of water glass. In the preparation process of slurry-coated gangue coarse aggregate, the mass ratio of gangue-based polymer to water is 1:0.38.
[0060] Table 1 Performance test results of fire-free grass bricks
[0061] .
[0062] From the performance test results of the above embodiments, it can be seen that the gangue-based low-carbon and fire-free grass bricks prepared by the present invention have high strength, good durability such as frost resistance, weathering resistance, carbonization resistance, water resistance, high solid waste utilization rate, low carbon emissions, good plant adaptability, good environmental coordination, energy saving and environmental protection, and are in line with the concept of circular economy and environmental protection.
[0063] The present invention has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the concept of the present invention, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present invention and will not be described in detail one by one here.
Claims
1. A carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick, characterized in that: The invention is prepared from the following raw materials in parts by weight: 260-520 parts of coal gangue-based polymer, 624-936 parts of coal gangue fine aggregate, 1144-1714 parts of slurry-coated coal gangue coarse aggregate, and 200-300 parts of water; The gangue-based polymer is made of the following raw materials in parts by weight: 110-220 parts of solid waste ultrafine powder, 110-220 parts of burned coal-based solid waste ultrafine powder, 0-22 parts of nano gangue powder, 10-118 parts of alkaline substances, 0-45 parts of gypsum, and 0-25 parts of inorganic salts; The slurry-coated gangue coarse aggregate is prepared by the following method: immersing the gangue coarse aggregate particles with a particle size of 5mm to 15mm into the gangue-based polymer slurry, shaking and then standing, and filtering the slurry after repeating 1 to 2 times, and then curing in a cool place for 25 to 30 days, the curing temperature is ≥15°C, and the material is kept in a wet state during the curing period; the gangue-based polymer slurry is composed of the gangue-based polymer and water in a mass ratio of 1:0.3 to 0.5; In terms of weight percentage, the alkaline substance is composed of the following specific surface area ≥ 600m 2 / kg of fine powder is composed of 50-100% carbide slag, 0-50% ultrafine steel slag powder, and 0-50% red mud; the ultrafine solid waste powder has the following specific surface area ≥600m 2 / kg of fine powder material composition: ultrafine granulated blast furnace slag powder 50-100%, ultrafine fly ash 0-50%; the ultrafine powder of burned coal-based solid waste has the following specific surface area ≥600m 2 / kg of fine powder composition: 50-100% calcined coal gangue ultrafine powder, 0-50% calcined coal slime ultrafine powder; the preparation method of the calcined coal gangue ultrafine powder is as follows: after the coal gangue powder is mixed with 0-20% of carbide slag, it is ground to a specific surface area of ≥300m 2 / kg, the powder under the sieve is calcined at 749℃ for 25-35min, and then ground to a specific surface area of ≥600m 2 / kg; The preparation method of the calcined coal slime ultrafine powder is as follows: take the coal slime produced in the coal washing process and mix it with 0-20% of carbide slag, calcine it at 600°C for 25-35min, and then grind it to a specific surface area of ≥600m 2 / kg.
2. The carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick according to claim 1 is characterized in that: The inorganic salt is at least one of carbonate, nitrate, chloride, metasilicate, silicate and water glass.
3. The carbonization-cured high-strength coal gangue-based low-carbon, fire-free grass-planting brick according to claim 1 is characterized in that: The specific surface area of the nano-coal gangue powder is > 240m 2 / g, particle size <30nm; the gypsum is at least one of desulfurized gypsum and phosphogypsum.
4. The carbonization-cured high-strength gangue-based low-carbon, fire-free grass-planting brick according to claim 1 is characterized in that: The gangue powder is obtained by crushing washed gangue into particles less than 5 mm by a jaw crusher and / or a roller crusher, and then grinding it in a ball mill for 30 to 90 minutes and then sieving out particles with a particle size greater than 0.212 mm.
5. The carbonization-cured high-strength gangue-based low-carbon, fire-free grass-planting brick according to claim 1 is characterized in that: The coal gangue fine aggregate is a granular material with a particle size of less than 5 mm obtained by crushing and screening the excavated coal gangue.
6. The method for preparing the carbonization-cured high-strength gangue-based low-carbon, fire-free grass-planting bricks according to claim 1, characterized in that: The steps include: A. Preparation of premix: Prepare the raw materials according to the raw material ratio described in claim 1, first pour the remaining raw materials except the gangue fine aggregate and the slurry-coated gangue coarse aggregate into a forced mixer for stirring, first stir slowly for 30 seconds, then add the gangue fine aggregate and the slurry-coated gangue coarse aggregate at a uniform speed, continue to stir slowly for 60 seconds, let it stand for 60 seconds, and then stir quickly for 60 seconds to complete the preparation of the premix; B. Forming of unburned grass-planting bricks: Pour the premix into the mold, turn on the vibration pump at the bottom of the brick-making machine until the premix is at the same level as the upper edge of the mold, and then turn off the vibration pump; move the pressing plate back to the initial position and open the pressing plate control valve to allow the pressing plate to move downward and fully contact the premix; turn on the upper vibration pump, and turn off the vibration pump when the pressing plate moves down to the set position, demold, and obtain the bricks; C. Curing of unfired grass bricks: The prepared unfired grass bricks are left to stand for 10 to 30 hours. After being formed, they are wrapped with plastic wrap and placed in an unventilated room at 15 to 25°C for curing for 3 to 5 days. Then, they are carbonized and cured in a sealed container for 3 to 5 days. The carbon curing conditions are: temperature 15 to 25°C, humidity 50% to 70%, and CO2 volume fraction > 15%.
Citation Information
Patent Citations
Baking-free coal gangue brick and preparation method thereof
CN106673563A
Coal-based solid waste geopolymer cementing material and preparation method thereof
CN112919854A
Fly ash-based geopolymer modified coal gangue concrete block and preparation method thereof
CN113845350A